2008
DOI: 10.1109/aswec.2008.4483215
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Evolution of Inheritance in Java OSS

Abstract: Previous studies of Object-Oriented (OO) software have reported avoidance of the inheritance mechanism and cast doubt on the wisdom of 'deep' inheritance levels. From an evolutionary perspective, the picture is unclear -we still know relatively little about how, over time, changes tend to be applied by developers. Our conjecture is that an inheritance hierarchy will tend to grow 'breadth-wise' rather than 'depth-wise'. This claim is made on the basis that developers will avoid extending depth in favour of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
5
14
0
Order By: Relevance
“…From the same figure, the maximum change of NOA takes place between versions 3 to 4. This trend was also observed in changes of number of methods in Nasseri et al (Nasseri et al 2008) suggesting that the system underwent major re-engineering between these two versions. From Figure 1, we see that DIT 1 and 2 is where the vast majority of activity takes place; developers tended to be relatively inactive at deeper levels of the inheritance hierarchy.…”
Section: Hsqldbsupporting
confidence: 56%
See 2 more Smart Citations
“…From the same figure, the maximum change of NOA takes place between versions 3 to 4. This trend was also observed in changes of number of methods in Nasseri et al (Nasseri et al 2008) suggesting that the system underwent major re-engineering between these two versions. From Figure 1, we see that DIT 1 and 2 is where the vast majority of activity takes place; developers tended to be relatively inactive at deeper levels of the inheritance hierarchy.…”
Section: Hsqldbsupporting
confidence: 56%
“…Figure 9 shows the net changes of attributes in SwingWT (max DIT 7, 22 versions and 522 classes). A peak in version 9 of the system was also observed in changes of methods in Nasseri et al ) and classes in Nasseri et al (Nasseri et al 2008). In version 9 of SwingWT, the number of attributes increases by 645, accompanied by 1929 methods and 160 classes.…”
Section: Tyrantmentioning
confidence: 77%
See 1 more Smart Citation
“…As part of a recent empirical study of the addition of classes to a system called JBoss [Nas08], over 4000 classes were added between one version (19 and 20). From version 20 to 21, over 4000 classes were removed from the system.…”
Section: Research Question Re-visitedmentioning
confidence: 99%
“…A recent study by Nasseri et al [Nasseri08] reported that 96% of incremental class changes over the course of the versions of four Java open-source systems studied were at inheritance levels 1 and 2 (where level 1 is immediately below Object). Only 4% of changes were made at levels 3 and below; this was largely because the majority of the system's classes were at DIT 1 and 2.…”
Section: 12mentioning
confidence: 99%